The relationship between frontal QRS-T angle and premature ventricular contraction burden in ambulatory 24-hour Holter - Göksel Çağırcı; Görkem Kuş (Acta Medica Alanya)
Aim: Frequent premature ventricular contractions (PVCs) can cause impaired ventricular function or dilatation of ventricular cavities. The frontal plane QRS-T [f(QRS-T)] angle is an indicator of instability in the electrophysiological properties of the myocardium and is associated with arrhythmias. The present study aimed to investigate whether f(QRS-T) angle, as a marker of ventricular repolarization heterogeneity, predicts premature ventricular contraction burden in ambulatory 24-hour Holter.Methods: The study included 100 patients. The patients were divided into two groups as ‘frequent PVC’ and ‘seldom PVC’ according to their PVC burden in 24-hour Holter monitoring. Laboratory and some ambulatory electrocardiography parameters, including frontal plane QRS-T angle, were compared between the two groups.Results: Frontal QRS-T angle (63.34±37.86° vs 23.46±14.29° p<0.001) was found to be wider in the Frequent PVC group. F(QRS-T) angle of ≥ 34° had a sensitivity of 82.2% and a specificity of 80% in indicating PVC load (AUC: 0.887 (0.824-0.950). In addition, a positive correlation was found between PVC burden and f(QRS-T) angle (r:0.429 p<0.001).Conclusion: The widening of f(QRS-T) angle could perhaps be considered as a surrogate marker of increased PVC burden in 24-hour Holter monitoring. Measuring f(QRS-T) angle in 12-lead ECG in patients with PVC may be a warning sign for increased PVC burden.